2023
DOI: 10.1021/accountsmr.2c00177
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Iron Sulfides: A Versatile Antibacterial Candidate with Multiple Mechanisms against Bacterial Resistance

Abstract: Conspectus Bacterial infections pose an ongoing threat to global human health, an issue of growing urgency due to the emergence of resistance against many currently available antibiotics. Recently, the World Health Organization (WHO) launched a global appeal for the development of novel antibiotics to combat this issue. Ideal antibiotics should possess specific antibacterial effects, without causing resistance. However, the discovery of different antibiotics is lagging the development of drug-resistant bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…FeS NPs have the ability to maintain and promote microbial species metabolism to mediate EET; 9 however, some studies have reported that FeS can inhibit the growth of organisms, including microorganisms, 17,42 plants, 43 and zebrafish. 44 For instance, Cui et al 17 demonstrated that a long-term operation (46 d) in microbial fuel cells led to excess iron sulfide nanoparticles accumulating on the outer layer cells, which might negatively affect the microbial metabolisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FeS NPs have the ability to maintain and promote microbial species metabolism to mediate EET; 9 however, some studies have reported that FeS can inhibit the growth of organisms, including microorganisms, 17,42 plants, 43 and zebrafish. 44 For instance, Cui et al 17 demonstrated that a long-term operation (46 d) in microbial fuel cells led to excess iron sulfide nanoparticles accumulating on the outer layer cells, which might negatively affect the microbial metabolisms.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, according to the trend of Fe 2+ production and the aggregation of iron-sulfur minerals on the cell surface, adjustments of the FeS synthesis rate and yield were also achieved by altering the initial S 2 O 3 2− precursor via self-regulation by S. oneidensis MR-1, while increasing the precursor concentration did not increase FeS biosynthesis, probably because excessive FeS was detrimental to S. oneidensis MR-1 metabolism. FeS NPs have the ability to maintain and promote microbial species metabolism to mediate EET; 9 however, some studies have reported that FeS can inhibit the growth of organisms, including microorganisms, 17,42 plants, 43 and zebrafish. 44 For instance, Cui et al 17 demonstrated that a long-term operation (46 d) in microbial fuel cells led to excess iron sulfide nanoparticles accumulating on the outer layer cells, which might negatively affect the microbial metabolisms.…”
Section: Characterization Of the Sch And Fes Npsmentioning
confidence: 99%
“…In addition, a nano-colloidal pyrite compound (“pyrite nanozyme”) has recently been shown to have a 3300-fold higher affinity for H 2 O 2 than Mag, with a more than 4000-fold higher catalytic activity ( Meng et al, 2021 ). It has also been shown that iron polysulfide particles possess POD, CAT and intrinsic glutathione oxidase (GSH-OXD)-like activity ( Xu et al, 2018 ; Cao et al, 2023 ). These iron sulfide colloids can decompose H 2 O 2 into free radicals and O 2 , promoting the release of polysulfides.…”
Section: Architectural Changes Of Iron Nanocolloids and Their Impact ...mentioning
confidence: 99%
“…Cao et al designed and synthesized a series of metastable iron sulfides, such as Fe 3 S 4 , Fe 1−x S, Fe 7 S 8 , and FeS. 108 They found that metastable iron sulfide has a multimode antibacterial mechanism, which can not only effectively kill a variety of Gram-positive and Gram-negative drug-resistant mutants but also eliminate bacteria in biofilms and cells. This mechanism is different from the traditional antibiotic bactericidal mechanism and therefore may provide a new antibacterial material for the resistance crisis.…”
Section: •−mentioning
confidence: 99%
“…Their experiment results showed that the PdFe/GDY nanozyme could consume GSH for bacterial disinfection with >99.99% killing effect, promote wound healing without significant toxicity both in vivo and in vitro, and can also be used as an effective antimicrobial agent for wound disinfection. Cao et al designed and synthesized a series of metastable iron sulfides, such as Fe 3 S 4 , Fe 1– x S, Fe 7 S 8 , and FeS . They found that metastable iron sulfide has a multimode antibacterial mechanism, which can not only effectively kill a variety of Gram-positive and Gram-negative drug-resistant mutants but also eliminate bacteria in biofilms and cells.…”
Section: Biomedical Applications Of Iron-based Nanozymesmentioning
confidence: 99%